Understanding "Hybrid Immunity": Comparison and Predictors of Humoral Immune Responses to Severe Acute Respiratory Syndrome Coronavirus 2 Infection (SARS-CoV-2) and Coronavirus Disease 2019 (COVID-19) Vaccines. (5th July 2022) - Epsi, Nusrat J; Richard, Stephanie A; Lindholm, David A; Mende, Katrin; Ganesan, Anuradha; Huprikar, Nikhil; Lalani, Tahaniyat; Fries, Anthony C; Maves, Ryan C; Colombo, Rhonda E; Larson, Derek T; Smith, Alfred; et al.
Abstract: Background: Comparison of humoral responses in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccinees, those with SARS-CoV-2 infection, or combinations of vaccine/ infection ("hybrid immunity") may clarify predictors of vaccine immunogenicity. Methods: We studied 2660 US Military Health System beneficiaries with a history of SARS-CoV-2 infection-alone (n = 705), vaccination-alone (n = 932), vaccine-after-infection (n = 869), and vaccine-breakthrough-infection (n = 154). Peak anti-spike–immunoglobulin G (IgG) responses through 183 days were compared, with adjustment for vaccine product, demography, and comorbidities. We excluded those with evidence of clinical or subclinical SARS-CoV-2 reinfection from all groups. Results: Multivariable regression results indicated that vaccine-after-infection anti-spike–IgG responses were higher than infection-alone ( P < .01), regardless of prior infection severity. An increased time between infection and vaccination was associated with greater post-vaccination IgG response ( P < .01). Vaccination-alone elicited a greater IgG response but more rapid waning of IgG ( P < .01) compared with infection-alone ( P < .01). BNT162b2 and mRNA-1273 vaccine-receipt was associated with greater IgG responses compared with JNJ-78436735 vaccine-receipt ( P < .01), regardless of infection history. Those with vaccine-after-infection or vaccine-breakthrough-infection had a more durable anti-spike–IgG response compared to infection-alone ( P < .01). Conclusions: Vaccine-receipt elicited higher anti-spike–IgG responses than infection-alone, although IgG levels waned faster in those vaccinated (compared to infection-alone). Vaccine-after-infection elicits a greater humoral response compared with vaccine or infection alone; and the timing, but not disease severity, of prior infection predicted these post-vaccination IgG responses. While differences between groups were small in magnitude, these results offer insights into vaccine immunogenicity variations that may help inform vaccination timing strategies. Abstract : Prior severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection followed by vaccination, or vice versa, provides a greater and more durable immunoglobulin G response than SARS-CoV-2 infection- or vaccine-induced immunity alone. The timing between SARS-CoV-2 infection and vaccination shapes the magnitude of post vaccine responses.